“Corpus Callosum” Mystic Region of the Brain - Selçuk Apak (Güncel Pediatri)
Corpus Callosum (CC) is located in the middle part of the brain. Although it’s presence known since centuries, some functions still could not be well understood. Structure of CC is somewhat different from other parts of brain and easily be affected from several factors during pre and post natal period. Agenesis or dysgenesis of corpus callosum can be a part of several genetic syndromes or by itself is associated with some somatic and psychiatric diseases. Recently US and MRI greatly help to discover the disorders of CC. In this paper, the importance of CC in pediatric disorders and the philosophique, anatomic, morphologic, filogenetic and ontogenetic features during historical periods will be reviewed. (Journal of Current Pediatrics 2009; 7: 142-6)